Implementation of Business Intelligence to Support Decision Making in Academic Information Systems - Risna Risna; Muhammad Syahrani (International Journal of Artificial Intelligence Research, 2026)
The rapid advancement of digital transformation has encouragedhigher education institutions to optimize the utilization of academicdata as a strategic asset for evidence-based decision-making. AlthoughAcademic Information Systems (AIS) continuously generatesubstantial volumes of academic data, these data are predominantlyused to support operational activities rather than strategic analysis andinstitutional planning. This study aims to develop a BusinessIntelligence (BI) implementation model for Academic InformationSystems by integrating a data warehouse, Extract, Transform, andLoad (ETL) processes, and interactive analytical dashboards tofacilitate data-driven decision-making